O006 A randomised trial of normothermic machine perfusion versus static cold storage in donation after circulatory death renal transplantation. (22nd July 2022) - Hosgood, SA; Callaghan, C; Wilson, C; Oniscu, GC; Phillips, BL; Bates, L; Smith, L; Nicholson, ML
Abstract: Introduction: Kidneys from donation after circulatory death (DCD) donors are more susceptible to cold storage (CS) injury and have a high risk of delayed graft function (DGF). This trial is the first to compare normothermic machine perfusion (NMP) to conventional CS in DCD kidney transplantation. Methods: In a multicentre randomised control trial, DCD kidneys were randomised to either NMP or CS. NMP kidneys were perfused for 60min with an oxygenated red-cell-based solution (36.0°C) The primary end point was DGF defined as the requirement for dialysis in the first 7days post-transplant. Secondary outcome measures included renal function up to 12 months posttransplant and patient/ graft survival. For all outcome measures a logistic regression model was used adjusted for cold ischaemic time, donor age, left/right kidney and centre. Results: February 2016-March 2020, 338 kidneys were randomised into the trial. Twenty-five kidneys did not undergo NMP due to logistical/technical difficulties but were included in an intention-to-treat analysis. Twenty-seven kidneys in the NMP and 21 in the CS group where not transplanted and excluded; 143 NMP and 147 CS kidneys were analysed. There was no significant difference in the rate of DGF (NMP 61% vs CS 58%; P=0.624). Secondary outcome measures demonstrated a significantly higher creatinine reduction ratio day 2(CRR2) (P=0.035) and significantly lower levels of serum creatinine across all timepoints in the NMP group (P=0.024). Conclusion: A short end period of NMP did not reduce rates of DGF in DCD kidneys. Secondary outcome measures suggest that NMP may improve renal function. Take-home message: This is the first randomised controlled trial of normothermic machine perfusion (NMP) in clinical transplantation. The results suggest that NMP may improve the renal function of DCD kidneys.